Plasma-assisted deposition of antimicrobial silver nanoparticles on medical textiles - Zille, Andrea (2019)
Two of the major problems in worldwide hospitals are the healthcare-associated infections (HAIs) and the skin and soft tissue infections (SSTIs). Every year mortality rates and health costs related to HAIs and SSTIs increases. Furthermore, the antibiotic resistance is moving faster than the development of new efficient antibiotic agents so, alternatives, for antimicrobial action, are urgently needed. Silver nanoparticles (AgNPs) have been used as antimicrobial agent in wound and burn dressings, surgical sutures and medical staff uniforms revealing a noble effect on Gram positive and Gram-negative bacteria, virus and fungi, including various drug resistant strains. AgNPs have improved properties compared with larger particles that allow a unique action due to the high surface to-volume ratio. However, there are some significant problems related with AgNPs based antimicrobial textiles due to the uncontrolled immbolization and release of AgNPs leading to excessive exposure. Several methods are used to incorporate AgNPs into fabrics, however, they often consume many chemicals, energy, time and usually required special equipment and have weak adhesion to the substrate. Dielectric barrier discharge (DBD) plasma treatment can be efficiently used as a pretreatment to activate the surface of the fabrics and improve the AgNPs adhesion. This is a dry environmental friendly and low cost technology since it may be produced at ambient conditions without any chemical product.